Deductive Verification of the Sliding Window Protocol - D. A. Chkliaev; V. A. Nepomniaschy (Моделирование и анализ информационных систем, 2012)
We consider the well-known Sliding Window Protocol which provides reliable and efficient transmission of data over unreliable channels. A formal proof of correctness for this protocol faces substantial difficulties caused by a high degree of parallelism which creates a significant potential for errors. Here we consider a version of the protocol that is based on selective repeat of frames. The specification of the protocol by a state machine and its safety property are represented in the language of the verification system PVS. Using the PVS system, we give an interactive proof of this property of the Sliding Window Protocol.